Conversation Cloud: A videoconferencing learning ecology for Thai undergraduate EFL learners. (December 2021) - Palungtepin, Mattanee
Abstract: This study investigated the use of cloud-based videoconferencing technology in the activity "Conversation Cloud" to provide Thai undergraduates with opportunities for authentic conversations with English speakers across the globe. Data included 115 Likert scale survey responses and content analysis of students' commentaries in the survey, consolidated with qualitative interviews with key respondents and the researcher's field notes. The study examined a videoconferencing environment on a macro level and attempted to identify influential variables as well as their relationships within the whole environment. Content analysis was conducted to systematically glean the most frequently mentioned variables from learner experience, revealing key elements and characteristics in an ecosystem of language learning. Emerging themes which provide insights regarding favorable conditions include the "organic" nature of the learning ecosystem, scaffolded learning, and diversity. The study aims to shed light on how a videoconferencing environment could be designed and created to enhance students' learning experience and facilitate their speaking progress in order for them to become confident English speakers in a global environment.